2007
DOI: 10.1002/ceat.200700033
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Pressure Drop and Holdup for Liquid‐Liquid Upflow through Vertical Pipes

Abstract: The present study has attempted to investigate pressure drop and holdup during simultaneous flow of two liquids through a vertical pipe. The liquids selected were kerosene and water. The measurements were made for phase velocities varying from 0.05-1.2 m/s for both liquids. The pressure drop was measured with a differential pressure transducer while the quick closing valve (QCV) technique was adopted for the measurement of liquid holdup. The measured holdup and pressure drop were analyzed with suitable theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Some of the researchers were found to have a disagreement pertaining to the factors that affect the losses of pressure in the pipes. Among others are Vuong et al [36], Vielma et al [35], Jana et al [37], Chakrabarti et al [38] and Trallero et al…”
Section: Investigation Of Pressure Dropmentioning
confidence: 97%
See 3 more Smart Citations
“…Some of the researchers were found to have a disagreement pertaining to the factors that affect the losses of pressure in the pipes. Among others are Vuong et al [36], Vielma et al [35], Jana et al [37], Chakrabarti et al [38] and Trallero et al…”
Section: Investigation Of Pressure Dropmentioning
confidence: 97%
“…Vielma et al [35] also stated that there was no significant effect of pressure drop during high oil superficial velocity at any water superficial velocity due to the presence of oil droplets in all flowing conditions. On the other hand, Jana et al [37] found that the in-situ proportion or liquid holdup has an effect on the pressure drop in a vertical section. They believed that the in-situ proportion is usually not equal in a liquid-liquid system due to the slip effect in which the lighter fluid moves faster than the heavier one.…”
Section: Investigation Of Pressure Dropmentioning
confidence: 97%
See 2 more Smart Citations
“…Input water fraction against the slip velocity ratio and water holdup in vertically dispersed flows. Alkaya [18] À3.5 4.0 6.9 9 Flores et al [1] 2.2 6.2 13.4 30 Jana et al [21] À0.2 8.1 14.0 48 Mukherjee et al [2] À2.1 7.2 8.5 38 Xu et al [11] 5.6 11.6 16.8 80 Figure 6. Comparison between experimental and predicted water holdups in horizontal flows.…”
Section: Model Developmentmentioning
confidence: 99%